The dynamic balance training instruments - Hwu, C. H. (International Journal of Sports Science and Engineering, 2008)
Based on the author with the technical background and studies TaiJiQuan, push-hand and boxing nearly three decades experience; early in the end of 1983, the author got the nationwide champion on 60kg push-hand competition in Taiwan, ROC, only by one and half a year push-hand practice without accepting any other martial arts training experience prior. Also through martial arts practicing experience and with the psychology experience of the author, concludes that the mass majority couldn`t get effective promoting on his fighting ability, is based on the learner`s worse mindset of the resistance that generate naturally by human-human practice mode, then the author tries to solve this problem of almost each learner certainly occurred within real practice. With a life time studying, the author with thorough understanding the essence of `the science of fighting techniques` then makes the scientific definition of the `in-fight`, and `out-fight`. Then from the above definitions drive out the fundamental theories. Again based on these fundamental theories, the author through the research and development then invented the elementary and professional training equipment of `the science of fighting techniques` that is `the dynamic balance training instrument`, which is able to use in broad range of training on all kinds of fighting techniques in the field of dynamic balance training. Caused by quoting the human-mechanism mode with the dynamic balance training instrument for the contestant training, is naturally and effectively prevent the necessarily and abiogenetically resistance mental state at human-human mode, it is easy to get valid improvement in the field of dynamic balance training. In future, this training concept and instrument it will force the contestant without any other choice to accept dynamic balance training, otherwise he is unable to stand still on the game field definitely. In 2008, because China sponsors the Olympic sports games in Beijing, the author ahead of time already with lot efforts through various different conducts tried to inform the leader of China, with this invention related theories and training implementation time schedule. But the decision maker of China government might not with the opportunity to receive this information; thus could not value this invention which is able to bring many extra medals for China in the Olympic 2008, also might not have the ability of foresightedness cognition this invention can make such enormous industrial system and huge commercial benefit to China. At here, the author is the first time to open this cooperation opportunity to all other nations in the world and any international enterprise that value this invention.